Valosine containing protein is a substrate of cAMP-activated boar sperm tyrosine kinase - Geussova, Gizela; Kalab, Petr; Peknicova, Jana (Molecular reproduction and development, 2002)
Previously we reported that treatment of boar sperm with cAMP-elevating drugs induces tyrosine phosphorylation of a triton-insoluble 93 kDa protein (p93). We have isolated p93 by preparative SDS electrophoresis and blotting from urea-extracted boar sperm and identified it as a valosine containing protein (VCP) by mass spectrometry and microsequencing. With the use of antibodies to VCP and phosphotyrosine (pY) we found that both p93 and VCP are poorly extractable with triton and are solubilized in > 6 M urea. Furthermore, VCP and p93 overlap on one and two dimensional (1 and 2D) electrophoretic gels, supporting the identity of p93 as a tyrosine-phosphorylated population of VCP. According to immunofluorescence, VCP is localized along the entire sperm tail, in the posterior ring, distal equatorial segment, and postacrosome. In addition, 9-12% sperm contained VCP in the acrosome. The cAMP-elevating treatment did not alter VCP localization but induced tail tyrosine phosphorylation in 15% sperm cells. In those sperm, VCP and pY colocalized in connecting piece and posterior ring.
Keywords: prasata; Valosin Containing Protein; protein obsahující valosin; Swine; Male; adenosintrifosfatasy; tyrosinkinasy; fosforylace; Phosphorylation; molekulární sekvence - údaje; Amino Acid Sequence; Spermatozoa; mužské pohlaví; elektroforéza v polyakrylamidovém gelu; proteiny buněčného cyklu; Animals; Electrophoresis, Polyacrylamide Gel; zvířata; Adenosine Triphosphatases; spermie; sekvence aminokyselin; Molecular Sequence Data; Protein-Tyrosine Kinases; Cell Cycle Proteins